Eco-Fashion: An Eco-Friendly Lifestyle Trend - lasaiba, Mohammad Amin (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2023)
This research examines the phenomenon of eco-fashion as an eco-friendly lifestyle trend and its impact on the fashion industry and consumer behaviour. With a desk research method, this study analyzes literature from various relevant academic sources, including journals, books, and industry reports, to understand eco-fashion's development and challenges. The results show that eco-fashion has become essential in the global effort to create a more sustainable fashion industry, driven by increasing consumer awareness of conventional fashion's environmental and social impacts. Despite challenges such as higher prices and lack of clear certification standards, technological innovation and changes in consumer behaviour provide hope for the future growth of eco-fashion. The research also highlights the importance of sustainable business models such as slow fashion and circular economy in reducing the fashion industry's negative environmental impact. In conclusion, eco-fashion has excellent potential to redefine the fashion industry in the future, with continued support from government, industry and consumers, as well as further research and innovation to overcome existing barriers